Smart hand gestures recognition using K-NN based algorithm for video annotation purposes - Malek Zakarya Alksasbeh; Ahmad H AL-Omari; Bassam A. Y. Alqaralleh; Tamer Abukhalil; Anas Abukarki; Ibrahim Alkore Alshalabi; Amal Alkaseasbeh (Institute of Advanced Engineering and Science, 2021)
Sign languages are the most basic and natural form of languages which were used even before the evolution of spoken languages. These sign languages were developed using various sign